USP25 Expression in Peripheral Blood Mononuclear Cells Is Associated With Bone Mineral Density in Women - Shen, Jianlin; Fu, Bowen; Wu, Yanjiao; Yang, Yang; Lin, Xiaoning; Lin, Haibin; Liu, Huan; Huang, Wenhua (Frontiers in Cell and Developmental Biology, 2022)
Osteoporosis is the most common metabolic bone disease in postmenopausal women. As precursors of osteoclasts, peripheral blood mononuclear cells (PBMCs) are accessible and considered to be suitable models for studying osteoporosis pathology. Ubiquitination is a crucial protein degradation system in bone metabolism. The aim of this study was to identify potential ubiquitination-related genes in PBMCs that are related to osteoporosis pathogenesis. Therefore, we performed an integrated analysis of osteoporosis-related microarray datasets. With the obtained ubiquitination-related gene set, a weighted gene co-expression network analysis (WGCNA) was performed. The results showed that genes in the turquoise modules were correlated with menopause, and 48 genes were identified as hub genes. A differential expression analysis revealed 43 differentially expressed genes in pre- and postmenopausal samples. After integrating the information on differentially expressed menopause-related genes, we found that several members of the ubiquitin-specific protease (USP) family (USP1, USP7, USP9X, USP16, and USP25) were highly expressed in postmenopausal samples, with the USP25 expression level significantly higher in low BMD samples among premenopausal samples (P=0.0013) and all samples(P=0.013). Finally, we verified the protein expression of USP25 in PBMCs by performing Western blot analysis, and the results were in line with the aforementioned results. Moreover, by assessing GTEx datasets, we found the USP25 expression level to be highly correlated with TRAF6 expression in whole blood. Our results revealed that the USP family may play important roles in menopause and that USP25, in particular, is related to osteoporosis pathogenesis.